Fostering digital adaptation in Islamic religious education through digital park space: Evidence from a secondary school - Khofifah Indar Syafi'iyah; Muchamad Suraji; Khoirotun Nikmah; Livia Ramadani (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2026)
Digital transformation has become an imperative in contemporary education, yet the readiness of teachers, students, and digital infrastructure remains a significant challenge, particularly in IRE (Islamic Religious Education), where technology integration is often limited. This study aims to examine the implementation of a digital park as a digital adaptation space for IRE learning through a comprehensive and in-depth analysis. A qualitative case study was conducted at SMAN 1 Babat using in-depth interviews, participant observation, and document analysis. Data were analyzed through thematic analysis and triangulation to enhance credibility and contextual validity. The findings reveal that the digital park functions as a digital adaptation ecosystem that supports the transformation of IRE learning by integrating physical spaces, technology, and digital systems. Its implementation encompasses planning, execution, and evaluation processes, contributing to the development of students’ digital literacy, collaboration, communication, and self-directed learning skills. However, disparities in teachers’ digital competencies and limitations in internet infrastructure remain key challenges. Sustainable implementation therefore requires strengthened digital infrastructure, continuous professional development for teachers, and the adoption of more adaptive and dynamic digital pedagogies. Although this study is limited to a single case and does not quantitatively assess program effectiveness, it offers practical and conceptual insights for schools and policymakers seeking to advance technology-enhanced IRE learning.